A novel post-1950 CE atmospheric 14C record for the tropics using absolutely dated tree rings in the equatorial Amazon - Santos, Guaciara M.; Granato-Souza, Daniela; Ancapichun, Santiago; Oelkers, Rose; Haines, Heather A.; De Pol Holz, Ricardo Hernán; Andreu-Hayles, Laia; Hua, Quan; Barbosa, Ana Carolina (My University, 2024)
In this study, we present a comprehensive atmospheric radiocarbon (14C) record spanning from 1940 to 2016, derived from 77 single tree rings of Cedrela odorata located in the Eastern Amazon Basin (EAB). This record, comprising 175 high-precision 14C measurements obtained through accelerator mass spectrometry (AMS), offers a detailed chronology of post-1950 CE (Common Era) 14C fluctuations in the Tropical Low-Pressure Belt (TLPB). To ensure accuracy and reliability, we included 14C-AMS results from intra-annual successive cuts of the tree rings associated to the calendar years 1962 and 1963 and conducted interlaboratory comparisons. In addition, 14C concentrations in 1962 and 1963 single -year cuts also allowed to verify tissue growth seasonality. The strategic location of the tree, just above the Amazon River and estuary areas, prevented the influence of local fossil-CO2 emissions from mining and trade activities in the Central Amazon Basin on the 14C record. Our findings reveal a notable increase in 14C from land -respired CO2 starting in the 1970s, a decade earlier than previously predicted, followed by a slight decrease after 2000, signaling a transition towards the fossil fuel era. This shift is likely attributed to changes in reservoir sources or global atmospheric dynamics. The EAB 14C record, when compared with a shorter record from Muna Island, Indonesia, highlights regional differences and contributes to a more nuanced understanding of global 14C variations at low latitudes. This study not only fills critical spatial gaps in existing 14C compilations but also aids in refining the demarcation of 14C variations over South America. The extended tree -ring 14C record from the EAB is pivotal for reevaluating global patterns, particularly in the context of the current global carbon budget, and underscores the importance of tropical regions in understanding carbon -climate feedbacks.
Keywords: single tree -rings; bomb peak; atmospheric circulation; atmospheric14c calibration; tlpb or inter-tropical convergence zone (itcz)